2006
DOI: 10.1016/j.engfracmech.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Local approach to fracture based prediction of the ΔT56J and shifts due to irradiation for an A508 pressure vessel steel

Abstract: Local approach to fracture based prediction of the ∆T56J and ∆TKIc 100 shifts due to irradiation for an A508 pressure vessel steel. Engineering Fracture Mechanics, Elsevier, 2006, 73, pp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
(70 reference statements)
5
28
0
Order By: Relevance
“…It predicts also that an increase of the yield strength (produced for instance by neutron irradiation or an increase in strain rate) leads to a reduction of the fracture toughness, K IC , for a given test temperature and a given specimen thickness. It has been shown that this prediction is in good agreement with experimental results (see Tanguy et al 2006;Pineau and Pardoen 2007).…”
Section: Figsupporting
confidence: 75%
“…It predicts also that an increase of the yield strength (produced for instance by neutron irradiation or an increase in strain rate) leads to a reduction of the fracture toughness, K IC , for a given test temperature and a given specimen thickness. It has been shown that this prediction is in good agreement with experimental results (see Tanguy et al 2006;Pineau and Pardoen 2007).…”
Section: Figsupporting
confidence: 75%
“…According to previous studies [35,39], Young's modulus E and Poisson's ration m were assumed to be independent of temperature and irradiation, and equal to 200 GPa and 0.3, respectively. Viscous parameters fk 1 ; n 1 g and fk 2 ; n 2 g aim at reproducing strain rate effects for both low and high strain rate, respectively.…”
Section: Identification Of the Constitutive Lawmentioning
confidence: 99%
“…Considering the thermomechanical history encountered in WPS cycles, an adaptation of the original model to account for the temperature dependence of the model parameters proposed in [39] will be used in this study. The rupture probability of a volume element is then no longer represented by r Ip but by x ¼ ðr Ip =r u Þ m where both r u and m may be temperature dependent.…”
Section: Cleavage Fracture Modelmentioning
confidence: 99%
“…In conclusion, non-metallic inclusions, second-phase particles, and grain boundaries are considered to be the best candidate sites for void nucleation and ductile failure. Tanguy et al (2006) have also reported that the presence of second-phase particles, such as lamellar cementite or martensite, are a source of void nucleation. Chen et al (2002) showed that lamellar cementite has a delayed deformation rate as compared to ferrite.…”
Section: Void Nucleation Mechanism At the Grain Boundaries And The Sementioning
confidence: 94%